The Sharia Economic Values of Transactions in Pekkabata Market - Afrianti, Afrianti; Jamilah, Sitti; Muliati, Muliati (IAIN Parepare, 2020)
This article discusses the process of al-bai’ transactions for traders, and the application of Islamic economic values ​​in al-bai’ transactions to traders in the Pekkabata market in Pinrang Regency. The purpose of this thesis research is to obtain empirical data about the al-bai’ process, and the application of Islamic economic values ​​in al-bai’ transactions to traders in the Pekkabata market in Pinrang Regency.